Dynamics of a Viral Infection Model with General Contact Rate between Susceptible Cells and Virus Particles - Chenxi Dai; Cui Ma; Lijuan Song; Kaifa Wang (Abstract and Applied Analysis)
This paper investigates the dynamic behavior of a viral infection model with general contact rate between susceptible host cells and free virus particles. If the basic reproduction number of the virus is less than unity, by LaSalle’s invariance principle, the disease-free equilibrium is globally asymptotically stable. If the basic reproduction number of the virus is greater than unity, then the virus persists in the host and the endemic equilibrium is locally asymptotically stable.